Intuitive analog circuit design - Thompson, Marc T. (Newnes, 2014)
This book describes intuitive and "back-of-the-envelope" techniques for designing and analyzing analog circuits, including transistor amplifiers (CMOS, JFET, and bipolar), transistor switching, noise in analog circuits, thermal circuit design, magnetic circuit design, and control systems
Includes bibliographical references and index. - Print version record
Keywords: Electronic circuit design; Analog electronic systems; Circuits électroniques; Calcul; Systèmes analogiques